1995
DOI: 10.1111/j.1365-2249.1995.tb08363.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD11b/CD18 antibodies reduce inflammation in acute colitis in rats

Abstract: SUMMARYThe influx of monocytes and neutrophils into the inflamed tissue could be an important aspect in the pathogenesis of inflammatory bowel disease (IBD). A membrane protein involved in the monocyte/neutrophil adherence to endothelium is CDllb/CDI8 or aM,82 (complement receptor type 3 = CR3). In the present study the role of CDII b/CDI8 in experimental IBD was studied by treatment with ED7 and OX42, two MoAbs against CDllb/CDI8. Colitis was induced in rats by a single, rectal administration of 30mg 2,4,6-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 28 publications
(31 reference statements)
5
62
0
Order By: Relevance
“…It has also been shown that anti-CR3 mAb treatments (administration of OX42) significantly reduced the inflammation of acute colitis in rats (47). In our study, CR3-expressing cells were significantly reduced in the 1G3-treated group when compared with the vehicle-treated group.…”
Section: Discussionsupporting
confidence: 68%
“…It has also been shown that anti-CR3 mAb treatments (administration of OX42) significantly reduced the inflammation of acute colitis in rats (47). In our study, CR3-expressing cells were significantly reduced in the 1G3-treated group when compared with the vehicle-treated group.…”
Section: Discussionsupporting
confidence: 68%
“…[41][42][43][44] Few studies have directly examined the role of these molecules during experimental colitis with these reports documenting modification of trinitrobenzene sulfonic acid (TNBS) colitis with anti-CD18 or CD11b/ CD18 antibodies. 45,46 We report here that the b 2 integrin LFA-1 (CD11a/CD18) plays an important pathological role, whereas Mac-1 (CD11b/CD18) provides a critical regulatory role in DSS-induced experimental colitis. Several possible explanations could account for the difference in outcome regarding CD11b.…”
Section: Discussionmentioning
confidence: 89%
“…The histological hallmarks of UC are the invasion of crypt epithelium and lamina propria by polymorphonuclear neutrophils (PMNs), disruption of epithelial lining, and ulceration in the colon. PMNs are believed to play a pivotal role in mediating tissue damage in UC (41)(42)(43). In humans, PMN accumulation is also observed in rectal biopsies of active UC patients (44,45).…”
Section: Discussionmentioning
confidence: 99%